Testicular cancer awareness among fifth and sixth-year medical students - Ayşe Emel Önal; Servet Yüce; Elif Nur Koçak (Springer, 2024)
Abstract Background and objective The aim of this study is to determine the knowledge, attitudes, and behaviors regarding testicular cancer and testicular self-examination (TSE) among medical faculty students in their last two semesters before beginning clinical practice. This study also investigates their beliefs about the importance and efficacy of these practices in early cancer detection. Materials and methods This descriptive study was conducted between October 1, 2018, and July 31, 2019, involving both male and female students in the 5th and 6th grades of a medical faculty. A total of 278 students participated, providing insights into their level of awareness and engagement with TSE practices. Results 52.2% of the students were aware of self-testicular examination, yet only 15.5% of male students reported performing TSE regularly. 13.3% of students reported receiving formal training on this topic during their medical education, and a mere 2.9% observed these examinations demonstrated in clinical settings. Champion's Health Belief Model Scale indicated average sensitivity scores of 11.01 ± 4.36, perceived severity of 20.58 ± 5.92, perceived benefits of 11.46 ± 2.99, perceived barriers at 10.14 ± 4.04, and self-efficacy scores at 18.64 ± 5.26. Conclusion and recommendations The findings suggest that while medical students recognize the seriousness and benefits of TSE, there is a notable gap in regular practice and educational exposure. Increased educational efforts are recommended to enhance sensitivity and self-efficacy related to testicular cancer screening among future healthcare providers.